The Problem of Political Leadership and the Electoral Process in Côte d’Ivoire - Sadovskaya, Lubow M. (Africana Studia, 2020)
The article focuses on the analysis of the current political situation in Côte d’Ivoire in the face of the presidential election campaign with the election due to take place in October 2020. The country might be led to another socio-political crisis. The events might be influenced by ethnic and religious factors and also the problem of president Ouattara’s third term of office. Another issue that should not be overlooked is the destabilizing role that might be played in the electoral process by the Ivorian army.